2023
DOI: 10.3389/fimmu.2023.1182556
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the immune response: sulfated archaeal glycolipid archaeosomes as an effective vaccine adjuvant for induction of humoral and cell-mediated immunity towards the SARS-CoV-2 Omicron variant of concern

Abstract: Liposomes composed of sulfated lactosyl archaeol (SLA) have been shown to be a safe and effective vaccine adjuvant with a multitude of antigens in preclinical studies. In particular, SLA-adjuvanted SARS-CoV-2 subunit vaccines based on trimeric spike protein antigens were shown to be immunogenic and efficacious in mice and hamsters. With the continued emergence of SARS-CoV-2 variants, we sought to evaluate next-generation vaccine formulations with an updated antigenic identity. This was of particular interest f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 47 publications
(58 reference statements)
0
7
0
Order By: Relevance
“…The surrogate neutralization assay was performed as in ref. 24 and is described in the Supplementary Methods section .…”
Section: Methodsmentioning
confidence: 99%
“…The surrogate neutralization assay was performed as in ref. 24 and is described in the Supplementary Methods section .…”
Section: Methodsmentioning
confidence: 99%
“…In more recent studies, researchers employed a semi-synthetic archaeal phospholipid (i.e., sulfated lactosyl archaeol) to encapsulate different antigens and to assess the potential of SLA glycolipid as an adjuvant system [75,76]. Their studies revealed that immunizing mice with variants of concern (VOC)-based vaccines, specifically Beta and Delta-based spike trimer antigens, resulted in improved neutralizing responses to spike proteins from the corresponding variant.…”
Section: Archaeal Lipids As Adjuvants and Vaccine Delivery Systemsmentioning
confidence: 99%
“…These researchers concluded that cell-mediated responses, which play important roles in the neutralization of intracellular infections, were stimulated to a significantly higher level with the SLA adjuvant when compared with the Adda S03-adjuvanted preparations. Consequently, further developed vaccines, which are better capable of targeting the SARS-CoV-2 variants, could be formulated via an optimized combination of adjuvant and antigen components [75,76].…”
Section: Archaeal Lipids As Adjuvants and Vaccine Delivery Systemsmentioning
confidence: 99%
“…This "copy-passed" vaccine strategy that "chased" the emerged VOC into a new batch of "improved" bivalent COVID-19 vaccines was often surpassed by fast-emerging and rapidly mutating Omicron lineages 13 . The sequences of Spike protein in the recently circulating EG.5, HV.1, and JN.1 Omicron subvariants have already undergone over 100 accumulated mutations, away from the recent XBB1.5-adapted bivalent vaccine 14,15,16 . The "improved" bivalent vaccine was only effective 4 to 29% against the Omicron subvariants, circulating in Winter 2022 14,15,16 , and its effectiveness decreased even further against the more recent divergent and highly transmissible EG.5, HV.1, and JN.1 Omicron subvariants, circulating in Winter pan-CoV vaccine strategy that incorporates highly conserved non-Spike antigens to induce broad, cross-protective immunity against past, present, and future VOCs 10,17,18 .…”
Section: Introductionmentioning
confidence: 99%